Emergency medical services use and its association with acute ischaemic stroke evaluation and treatment in Singapore. Issue 2 (8th April 2020) - Xu, Hanzhang; Xian, Ying; Woon, Fung Peng; Bettger, Janet Prvu; Laskowitz, Daniel T; Ng, Yih Yng; Ong, Marcus Eng Hock; Matchar, David Bruce; De Silva, Deidre Anne
Abstract : Background: Emergency medical services (EMS) is a critical link in the chain of stroke survival. We aimed to assess EMS use for stroke in Singapore, identify characteristics associated with EMS use and the association of EMS use with stroke evaluation and treatment. Methods: The Singapore Stroke Registry combines nationwide EMS and public hospital data for stroke cases in Singapore. Multivariate regressions with the generalised estimating equations were performed to examine the association between EMS use and timely stroke evaluation and treatment. Results: Of 3555 acute ischaemic patients with symptom onset within 24 hours admitted to all five public hospitals between 2015 and 2016, 68% arrived via EMS. Patients who used EMS were older, were less likely to be female, had higher stroke severity by National Institute of Health Stroke Scale and had a higher prevalence of atrial fibrillation or peripheral arterial disease. Patients transported by EMS were more likely to receive rapid evaluation (door-to-imaging time ≤25 min 34.3% vs 11.1%, OR=2.74 (95% CI 1.40 to 5.38)) and were more likely to receive intravenous tissue plasminogen activator (tPA, 22.8% vs 4.6%, OR=4.61 (95% CI 3.52 to 6.03)). Among patients treated with tPA, patients who arrived via EMS were more likely to receive timely treatment than self-transported patients (door-to-needle time ≤60 min 52.6% vs 29.4%, OR=2.58 (95% CI 1.35 to 4.92)). Conclusions: EMS use is associated with timely stroke evaluation and treatment in Singapore. Seamless EMS-Hospital stroke pathways and targeted public campaigns to advocate for appropriate EMS use have the potential to improve acute stroke care.